FAKTOR-FAKTOR YANG MEMPENGARUHI PETANI KARET (Hevea Brasiliensis) MENJUAL BOKAR KE TENGKULAK (STUDI KASUS) DESA LEKIS REJO KECAMATAN LUBUK RAJA KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2019)
This study aims to determine Factors affecting rubber farmers sell bokar to middlemen (case study) village lekis rejo Lubuk Raja district of Ogan Komering Ulu Regency. This research was conducted in Lekis Rejo Village, Lubuk Raja Sub-District, Ogan Komering Ulu Regency, where the determination of the area was done purposively (purposive). Sampling method used in this research is simple random sampling method. The results of this study are factors that significantly affect the decision of rubber farmers to sell bokar to the middleman is Bokar Price (X1), Kinship Relationship (X2), and Loan Fee (X3).